Linkages and development of local industrial space: Research in the key economic region of Southern Vietnam - Nguyen Chi Hai; Huynh Ngoc Chuong; Trung Tra-Van (Cogent Economics & Finance, 2022)
The aim of this study is not only to define the industrial development space of the region in Vietnam, but also to assess the linkage in local industrial development. Research space in the Southern Key Economic Region-Vietnam's most vibrant industrial production region-is based on the approach in both aspects: output value and agglomeration of production enterprises through the number of businesses. By taking a diversified approach from defining the growth linkage indicator to simulating the industrial structure pattern by the network, and using the regression model with the industrial production enterprise data of the Region in the period 2011 - 2019. The research result shows that there has been a significant increase in the linkage to the development of industrial space in the Region. Besides, the pattern of industrial development space of the Region has both increased the production value in the central areas and spread the industrial bases established in other localities in the Region. From scientific findings, this paper gives policy implications as well as contributes to some improvements in assessing, analyzing and verifying industrial development space in the locality, especially for developing economies like Vietnam.
Keywords: 330; Regional industrial development; industrial space; industrial linkage; Vietnam; Revealed Comparative Advantage (RCA)